Nonlinear fiber optics - Agrawal, G. P. (Govind P.), 1951- (Burlington, MA ; London : Academic Press, 2007)
Since the 3rd edition appeared, a fast evolution of the field has occurred. The fourth edition of this classic work provides an up-to-date account of the nonlinear phenomena occurring inside optical fibers. The contents include such important topics as self- and cross-phase modulation, stimulated Raman and Brillouin scattering, four-wave mixing, modulation instability, and optical solitons. Many new figures have been added to help illustrate the concepts discussed in the book. New to this edition are chapters on highly nonlinear fibers and and the novel nonlinear effects that have been observed in these fibers since 2000. Such a chapter should be of interest to people in the field of new wavelengths generation, which has potential application in medical diagnosis and treatments, spectroscopy, new wavelength lasers and light sources, etc. * Continues to be industry bestseller providing unique source of comprehensive coverage on the subject of nonlinear fiber optics * Fourth Edition is a completely up-to-date treatment of the nonlinear phenomena occurring inside optical fibers * Includes 2 NEW CHAPTERS on the properties of highly nonlinear fibers and their novel nonlinear effects.
CH1 Introduction; CH2 Pulse Propagation in Fibers; CH3 Group-Velocity Dispersion; CH4 Self-Phase Modulation; CH5 Optical Solitons; CH6 Polarization Effects; CH7 Cross-Phase Modulation; CH8 Stimulated Rman Scattering; CH9 Stimulated Brillouin Scattering; CH10 Four-Wave Mixing; CH11 Highly Nonlinear Fibers; CH12 Novel Nonlinear Phenomena; APP A System of Units; -- APP B Numerical Code for the NLS Equation; APP C List of Acronyms.
Previous ed.: 2001.
Includes bibliographical references and index.
Keywords: Fiber optics; Nonlinear optics; Electronic books